Effect of brewery effluent inhibitors on Rhodotorula toruloides NCYC 921 cells grown in pure and mixed cultures at pH 4 and 6 - Dias, Carla (2022)
ABSTRACT: The presence of inhibitor compounds in the culture medium can cause severe effects on the microorganisms cells. Brewery wastewaters present organic acids (acetic, propionic and butyric acids) which can severely affect yeast cells metabolism, when grown in pure cultures, although in mixed cultures they are able to develop. To understand the physiological changes on Rhodotorula toruloides (formerly Rhodosporidium toruloides) cells when fermenting in the presence of the organic acids present in brewery wastewater, pure and mixed cultures with the microalga Tetradesmus obliquus were performed in a synthetic medium containing the same organic acids concentrations that are present in brewery wastewater at pH 4 and 6. It was concluded that, at pH 4, the organic acids effects in the yeast cells were much more toxic than at pH 6. Moreover, mixed cultures can be an advantage over heterotrophic pure cultures as the microalga is able to contribute for the consumption of potential inhibitors for the yeast.